Efficient and Cost-Effective Single Nucleotide Polymorphism Detection with Different Fluorescent Applications. (October 2001) - Aydin, A.; Baron, H.; Bähring, S.; Schuster, H.; Luft, F.C.
Three methods—5′ nuclease assay with TaqMan ®, minisequencing, and oligonucleotide ligation assay (OLA)—were compared to detect five single nucleotide polymorphisms (SNPs) in three separate genes. Each method had advantages and disadvantages. The 5′ nuclease assay was the fastest and required only a single step. OLA was the most time consuming to optimize, but once running it was the least expensive method. Minisequencing was universal; however, the technique was also the most expensive. All three methods were reliable and highly effective. Investigators must consider their goals in terms of time, sample number, and expense when selecting among these genotyping techniques.